Syntactic comprehension and working memory in children with specific language impairment, autism or Down syndrome. (July 2015) - Fortunato-Tavares, Talita; Andrade, Claudia R. F.; Befi-Lopes, Debora; Limongi, Suelly O.; Fernandes, Fernanda D. M.; Schwartz, Richard G.
Abstract This study examined syntactic assignment for predicates and reflexives as well as working memory effects in the sentence comprehension of children with Specific Language Impairment (SLI), Down syndrome (DS), high functioning Autism (HFA) and Typical Language Development (TLD). Fifty-seven children (35 boys and 22 girls) performed a computerised picture-selection sentence comprehension task. Predicate attachment and reflexive antecedent assignment (with working memory manipulations) were investigated. The results showed that SLI, HFA and DS children exhibited poorer overall performance than TLD children. Children with SLI exhibited similar performance to the DS and HFA children only when working memory demands were higher. We conclude that children with SLI, HFA and DS differ from children with TLD in their comprehension of predicate and reflexive structures where the knowledge of syntactic assignment is required. Working memory manipulation had different effects on syntactic comprehension depending on language disorder. Intelligence was not an explanatory factor for the differences observed in performance.